2011
DOI: 10.1038/cr.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Caspase cleavage of cytochrome c1 disrupts mitochondrial function and enhances cytochrome c release

Abstract: Mitochondrial catastrophe can be the cause or consequence of apoptosis and is associated with a number of pathophysiological conditions. The exact relationship between mitochondrial catastrophe and caspase activation is not completely understood. Here we addressed the underlying mechanism, explaining how activated caspase could feedback to attack mitochondria to amplify further cytochrome c (cyto.c) release. We discovered that cytochrome c1 (cyto.c1) in the bc1 complex of the mitochondrial respiration chain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…The organization of the mitochondrial electron transport chain is a subject of intense debate at present, where two different models are being considered: the fluid model, that proposes a random organization for individual respiratory protein components, and the solid model, suggesting a stable association between individual complexes [6][7][8]. Apart their role in respiration, Cc and Cc 1 are clearly involved in the development of programmed cell death [9][10][11][12][13][14][15]. Such a dual role of Cc is regulated by post-translational modifications -namely, phosphorylation and nitration of tyrosine residues -that affect the binding of Cc to its physiological counterparts, either in the mitochondria or in the cytoplasm [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The organization of the mitochondrial electron transport chain is a subject of intense debate at present, where two different models are being considered: the fluid model, that proposes a random organization for individual respiratory protein components, and the solid model, suggesting a stable association between individual complexes [6][7][8]. Apart their role in respiration, Cc and Cc 1 are clearly involved in the development of programmed cell death [9][10][11][12][13][14][15]. Such a dual role of Cc is regulated by post-translational modifications -namely, phosphorylation and nitration of tyrosine residues -that affect the binding of Cc to its physiological counterparts, either in the mitochondria or in the cytoplasm [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…4A and 4B). It has been reported that caspase-3 amplifies Cytc release and mitochondria fragmentation by cleaving CYC1 during mitochondria-dependent apoptosis [11]. In the mitochondrial electron transport chain, CYC1 directly interacts and stabilizes Cytc.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent study reported that CYC1 cleavage by caspase-3 disrupts mitochondrial function and enhances Cyt c release and apoptosis [11]. Thus, we speculated that CYC1 downregulation in OS might sensitize OS cells to apoptotic induction by TRAIL through promoting Cyt c release.…”
Section: Introductionmentioning
confidence: 97%
“…The other pro-apoptotic or antiproliferative protein genes downregulated were DAPK3 (Kawai et al, 1998), BMF (Puthalakath et al, 2001), RBL2 (Dick, 2007), RBBP2 (Chicas et al, 2012), BNIP3 (Burton et al, 2013), APP (Takahashi et al, 2009) Table S2). Similarly, anti-apoptotic/cell proliferation genes downregulated are CACNB4 (Tadmouri et al, 2012), TNFRSF11B (Oliver et al, 2013), CAPN6 (Rho et al, 2008), GRB2 (Kraskouskaya et al, 2013), TRAF6 (Wong et al, 1999), BZRP (Maaser et al, 2002), TNFRSF6B (Chen et al, 2010), RAF1 (McPhillips et al, 2006), CYC1 (Zhu et al, 2012), and HSPD1 (Ghosh et al, 2008) (Supplementary Table S2). …”
Section: Discussionmentioning
confidence: 99%